Outcome of Prophylactic Bogota Bag Application in Midline Laparotomy Wound Closure Versus Retention En Masse Closure Using Prolene Sutures in patients with Intra-Abdominal Hypertension - Naveed, Muhammad; hassan, Maazul; Ahmad Khan, Rizwan; Khaliq Khan, Fareeha; Ara, Jahan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the outcome of prophylactic bogota bag versus prolene retention sutures in patients with raised intra-abdominal pressure. Methodology: All the patients fulfilling the inclusion criteria presenting to emergency with the diagnosis of trauma, peritonitis and intestinal obstruction, were admitted as per protocol in south surgical unit, Mayo Hospital Lahore. Before laparotomy, their intra- abdominal pressure was measured using intra-vesical folleys catheter. Half of the closures were done using bogota bag and half closures using the prolene retention sutures. The patients were assessed for development of intra abdominal hypertension and wound dehiscence for a period of one week after their surgery. Results: Independent sample t test has applied to evaluate the difference between hospital length of stay between the patients treated with bogota bags and retention suture. The test was significant statistically i.e. p<0.05.Chi square analysis was performed to evaluate the association between wound dehiscence and intra abdominal pressure treated with bogota bag and p<0.05, hence the test was significant statistically. Conclusions: Bogota bag application is associated with lesser complications as compared to retention suture application in intra-abdominal hypertension.